Ascorbate Peroxidase Neofunctionalization at the Origin of APX-R and APX-L: Evidence from Basal Archaeplastida - Fernanda Lazzarotto; Paloma Koprovski Menguer; Luiz-Eduardo Del-Bem; Marcel Zámocký; Márcia Margis-Pinheiro (Antioxidants, 2021)
Ascorbate peroxidases (APX) are class I members of the Peroxidase-Catalase superfamily, a large group of evolutionarily related but rather divergent enzymes. Through mining in public databases, unusual subsets of APX homologs were identified, disclosing the existence of two yet uncharacterized families of peroxidases named ascorbate peroxidase-related (APX-R) and ascorbate peroxidase-like (APX-L). As APX, APX-R harbor all catalytic residues required for peroxidatic activity. Nevertheless, proteins of this family do not contain residues known to be critical for ascorbate binding and therefore cannot use it as an electron donor. On the other hand, APX-L proteins not only lack ascorbate-binding residues, but also every other residue known to be essential for peroxidase activity. Through a molecular phylogenetic analysis performed with sequences derived from basal Archaeplastida, the present study discloses the existence of hybrid proteins, which combine features of these three families. The results here presented show that the prevalence of hybrid proteins varies among distinct groups of organisms, accounting for up to 33% of total APX homologs in species of green algae. The analysis of this heterogeneous group of proteins sheds light on the origin of APX-R and APX-L and suggests the occurrence of a process characterized by the progressive deterioration of ascorbate-binding and catalytic sites towards neofunctionalization.